The Xiangya Ocular Tumor Bank: A Disease-Specific Biobank for Advancing Translational Research Into Ocular Tumors - Gao, Zhaolin; Tan, Jia; Wang, Sha; Yu, Haiyang; Zhou, Ziyu; Zhang, Yun; Zhou, Mushi; Xia, Xiaobo; Yao, Fei; Huang, Jufang (Frontiers in Medicine, 2022)
The pathogenesis and etiology of various ocular tumors remain largely unclear, limiting the development of diagnostic and treatment approaches for such tumors. Tissue samples from patients are also valuable resource to elucidate mechanisms underlying tumorigenesis. Here we present the early phase setup of an ocular tumor biobank at Xiangya Hospital. Blood and tissue samples along with associated clinical data were obtained from patients who underwent surgery in the Department of Ophthalmology of Xiangya Hospital from December 1, 2018 to January 31, 2020. Standardized operating protocols were developed for the collection, transportation, processing and preservation of ocular tumor samples. A total of 92 clinical cases suffered from 21 types of eye tumors and several undiagnosed eye diseases were covered. A total of 846 samples were preserved in the ocular tumor biobank, including 356 blood samples (42.1%), 324 plasma samples (38.3%), and 166 tissue samples (19.6%). Using the clinical data, we analyzed the prevalence of malignant ocular tumors in association with variables of age, gender, tumors' location and size, and presenting complaints of lump and proptosis. The factors predictive of malignant ocular tumors, included gender (B = 1.599; P = 0.025) and the symptom of proptosis (B = −2.534; P = 0.001). Overall, the setup of clinically-based ophthalmologic biobank could support pathological and translational research into ocular tumors.